2003
DOI: 10.1136/bjo.87.9.1151
|View full text |Cite
|
Sign up to set email alerts
|

Late and very late initial probing for congenital nasolacrimal duct obstruction: what is the cause of failure?

Abstract: Aims: To find the cure rate of late (second year of age) and very late (3-5 years of age) initial probing for congenital nasolacrimal duct obstruction (CNLDO) and to identify the factors contributing to the failure rate of the probing in older children. Methods: In a prospective interventional case series study, 169 eyes of 125 consecutive patients (1-5 years old) with CNLDO underwent probing under general anaesthesia. Cure was defined as absence of tearing and discharge in the affected eye. Results: 138 eyes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
5
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 18 publications
11
125
5
9
Order By: Relevance
“…In this study, an overall success rate of 84% was found, which is comparable with the success rate in early probing done around the first year of life. Kashkouli et al [10] , Elmansoury et al [11] , Zwaan et al [12] , and Honavar et al [13] found similar high success rate over 80%…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this study, an overall success rate of 84% was found, which is comparable with the success rate in early probing done around the first year of life. Kashkouli et al [10] , Elmansoury et al [11] , Zwaan et al [12] , and Honavar et al [13] found similar high success rate over 80%…”
Section: Discussionmentioning
confidence: 87%
“…These children may represent the pool of children with more complicated type of obstruction. Kashkouli et al [10] and Honavar et al [13] showed that the complex CNLDO was more likely to be found in older children, with subsequent lower success rate. Kushner [18] even suggested that a reasonable approach to older children with a CNLDO is to plan a probing procedure with possible alternative surgical plans if a…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have suggested that the success rate of probing is dictated not by the age at probing, but by the type of obstruction. [13][14][15][16][17] Simple obstructions at the valve of Hasner are the most common, but more complex anomalies do exist, which may be less amenable to disruption by simple probing alone. Endoscopic-assisted probing facilitates visualisation of the probe in the membranous nasolacrimal duct and in the inferior meatus of the nose.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was conducted to evaluate the success rate of primary nasolacrimal duct probing in children greater than 2 years of age where many authors believe the procedure has a low success rate. [6,7] …”
Section: Introductionmentioning
confidence: 99%